2016
DOI: 10.1080/08916934.2016.1191475
|View full text |Cite
|
Sign up to set email alerts
|

Association of established thyroid peroxidase autoantibody (TPOAb) genetic variants with Hashimoto’s thyroiditis

Abstract: Hashimoto's thyroiditis (HT) is the most common form of autoimmune thyroid diseases (AITD) characterized by progressive destruction of thyroid tissue that may lead to hypothyroidism. High thyroid autoantibodies against thyroid peroxidase (TPOAb) levels are present in 90% of patients with HT and serve as a clinical marker for the detection of early AITD/HT. The main aim of our study was to test whether recently identified genetic variants associated with TPOAb are also involved in HT development. A total of 504… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…These results seemed to reflect that certain loci of above genes could be associated with AITDs Uyghur patients in [20,21]. In recent decades, a number of SNPs in the TPO gene have been genotyped and different loci showed different effect on ATIDs (both GD and HT, or respectively), which further clarified the important role of TPO played in the development of AITDs [21][22][23][24]. TG is a 660-kDa glycoprotein, which accounts for about 75%-80% of the total thyroid protein [25,26] and deserves to be a major AITDs susceptibility gene.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…These results seemed to reflect that certain loci of above genes could be associated with AITDs Uyghur patients in [20,21]. In recent decades, a number of SNPs in the TPO gene have been genotyped and different loci showed different effect on ATIDs (both GD and HT, or respectively), which further clarified the important role of TPO played in the development of AITDs [21][22][23][24]. TG is a 660-kDa glycoprotein, which accounts for about 75%-80% of the total thyroid protein [25,26] and deserves to be a major AITDs susceptibility gene.…”
Section: Discussionmentioning
confidence: 76%
“…In our first genome screen, performed with 100 AITDs Uyghur patients (50 GD and 50 HT) and 50 Uyghur controls, seven SNPs of four genes showed evidence for linkage with AITDs Uyghur patients (Tables 2 and 3): four SNPs (rs62117031, rs62117032, rs4278970 and rs4927631) of TPO gene and one SNP (rs2702998) of TG gene elevated in AITDs patients; otherwise rs2284735 of TSHR gene and rs16843742 of PTPRC gene received an opposite consequence. These results seemed to reflect that certain loci of above genes could be associated with AITDs Uyghur patients in [20,21]. In recent decades, a number of SNPs in the TPO gene have been genotyped and different loci showed different effect on ATIDs (both GD and HT, or respectively), which further clarified the important role of TPO played in the development of AITDs [21][22][23][24].…”
Section: Discussionmentioning
confidence: 93%
“…They suggested that genetic variations in or near the TPO gene are associated with HT. 2 Balmiki et al have demonstrated that two TPO gene polymorphisms, namely Thr725Pro (rs732609) and Asp666Asp (rs1126797), had a significant correlation with those of Indian patients with hypothyroidism. 15 Similarly, we were also able to show the significant relationship between the Thr725Pro (A2173C) gene polymorphism of TPO and patients who had elevated serum TSH, but not FT3 and FT4, who were identified as having subclinical hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Subclinical hypothyroidism (SCH) is defined as high serum thyrotropin or thyroid stimulating hormone (TSH) and normal levels of free thyroxine (FT4). 3 Subclinical hypothyroidism is mild thyroid failure: it is a common condition with a prevalence of 3% to 8% in the population without known thyroid disease.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a recently identified type of natural bispecific antibody against TPO and Tg may play a protective role in the pathogenesis of HT [20]. Extensive studies conducted by various groups on genetic loci associated with the presence of TPOAbs revealed their localization, for example, in the HLA region and inside or near genes encoding TPO, TSH receptor (TSHR), and Tg [21][22][23][24][25][26][27].…”
Section: Characteristics Of Tpoabsmentioning
confidence: 99%